Ferroelectric domain structure and atomic-scale phase distribution in a Pb(Mg1/3Nb2/3)O3-PbTiO3 single crystal. Issue 3 (1st February 2022) - Wang, Ruoyu; Jiang, Yixiao; He, Neng; Li, Xiang; Yao, Tingting; Zheng, Limei; Chen, Chunlin; He, Lianlong; Ye, Hengqiang
Abstract: Lead-based relaxor ferroelectric crystals, such as Pb(Mg1/3 Nb2/3 )O3 -PbTiO3, are promising for functional applications due to their outstanding ferroelectric properties. Revealing ferroelectric domain structure and phase distribution at the nanoscale are important to understand the basic theory of ferroelectricity and promote their practical applications. In this study, the ferroelectric domain structure and atomic-scale phase distribution in a Pb(Mg1/3 Nb2/3 )O3 - 35 at.% PbTiO3 single crystal in the region of morphotropic phase boundary are systematically investigated by a combination of optical microscopy, scanning electron microscopy, and aberration-corrected transmission electron microscopy. It is found that 90° and 180° coarse domains are formed simultaneously in the ferroelectric single crystal. Moreover, there are tweed-like nano-domains formed inside each coarse single domain. Through careful investigations of distribution of stress and tetragonality, it is revealed that the tweed-like nano-domains are composed of nano-sized rhombohedral (R), monoclinic (M), and tetragonal (T) phases. The nano-scale T, M, R phases have the best, moderate, and lowest ferroelectricity, respectively.